Pengaruh edukasi gizi dengan video animasi terhadap pengetahuan dan sikap gizi seimbang siswa tunarungu di SMPLB-B Surabaya - Nirmalasari, Nisa Naila; Nur Afifah, Choirul Anna (Jurnal SAGO Gizi dan Kesehatan, 2026)
Background: Adolescence is a phase of significant physical change, making it important to meet nutritional needs. Malnutrition and overnutrition are problems encountered in deaf adolescents. The poor nutritional status of deaf children is caused by a lack of nutritional knowledge. Efforts that can be made include providing nutritional education with the aim of improving knowledge and attitudes related to balanced nutrition.Objectives: To determine the effect of nutrition education using animated videos on the knowledge and attitudes regarding balanced nutrition of deaf students at SMPLB-B Karya Mulia Surabaya.Methods: This study used a pre-experimental design with a one-group pre-test post-test design without a control group. The population consisted of 23 students from SMPLB-B Karya Mulia Surabaya. The sample was selected using total sampling. Data were collected using knowledge questionnaires and attitude questionnaires. Data processing consists of editing, coding, scoring, and cleaning. Data analysis was performed using the Wilcoxon statistical test.Results: There was a significant effect on improving students knowledge and attitudes after providing nutrition education using animated videos (p=0.001). There is an increase in the average knowledge score of 25.65 and thereis an increase in the average attitude score of 6.52.Conclusion: There is an effect of animated video media as a nutrition education media related to balanced nutrition on the knowledge and attitudes of deaf students of SMPLB-B Karya Mulia Surabaya.